Pressure-induced magnetic collapse and metallization of TlF e1.6 S e2 - Naumov, P. G.; Filsinger, K.; Shylin, S. I.; Barkalov, O. I.; Ksenofontov, V.; Qi, Y.; Palasyuk, Taras; Schnelle, W.; Medvedev, S. A.; Greenblatt, M.; Felser, Claudia (Physical Review B, 2017)
The crystal structure, magnetic ordering, and electrical resistivity of TlFe1.6Se2 were studied at high pressures. Below ∼7GPa, TlFe1.6Se2 is an antiferromagnetically ordered semiconductor with a ThCr2Si2-type structure. The insulator-to-metal transformation observed at a pressure of ∼7GPa is accompanied by a loss of magnetic ordering and an isostructural phase transition. In the pressure range ∼7.5-11GPa a remarkable downturn in resistivity, which resembles a superconducting transition, is observed below 15 K. We discuss this feature as the possible onset of superconductivity originating from a phase separation in a small fraction of the sample in the vicinity of the magnetic transition.
CRIS-Team Scopus Importer:2022-04-14